2001
DOI: 10.1152/ajpregu.2001.280.3.r730
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial adrenergic and cholinergic receptor function in hypoxia: correlation with O2 transport in exercise

Abstract: The time course of changes in rat myocardial alpha(1)- and beta-adrenoceptors and of muscarinic cholinergic (M-Ach) receptor characteristics was studied parallel with the changes in exercise systemic O(2) transport during a 21-day period of hypoxia (barometric pressure 380 Torr) to assess the effects of receptor modification during acclimatization on maximal exercise capacity. Hypoxia resulted in polycythemia, pulmonary hypertension, right ventricular hypertrophy, and transient left ventricular weight loss. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 25 publications
6
49
1
Order By: Relevance
“…As water consumption usually decreases at the beginning of hypoxic exposure, acetazolamide treatment started 2 days before hypoxia in the preventive group to obtain an adequate dose of acetazolamide. In curative-treated rats, the treatment began after 10 days of hypoxic exposure, as it has been previously reported that pulmonary hypertension as well as Hb concentration remain unchanged from day 10 to day 21 [1,8]. After the first day of acetazolamide treatment, we observed an important increase in water consumption in rats, demonstrating that acetazolamide was also taken well in curative treatment.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…As water consumption usually decreases at the beginning of hypoxic exposure, acetazolamide treatment started 2 days before hypoxia in the preventive group to obtain an adequate dose of acetazolamide. In curative-treated rats, the treatment began after 10 days of hypoxic exposure, as it has been previously reported that pulmonary hypertension as well as Hb concentration remain unchanged from day 10 to day 21 [1,8]. After the first day of acetazolamide treatment, we observed an important increase in water consumption in rats, demonstrating that acetazolamide was also taken well in curative treatment.…”
Section: Discussionsupporting
confidence: 76%
“…Both preventive groups received acetazolamide 2 days before entering the hypobaric chamber, while curative groups received acetazolamide after 10 days of hypoxic exposure, which has previously been shown to significantly increase pulmonary arterial pressure (PAP) [1]. Rats undergoing chronic hypoxic exposure were housed for 21 days in a hypoxic chamber connected to a gas pump where air was circulated at a pressure of 380 mmHg (5,500 m altitude above sea level).…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Favret et al [ 79 ], however, showed that the density of rat right ventricular β -adrenoceptors was signifi cantly elevated after just 30 min of hypoxia, but it subsequently declined to values below those found in normoxia.…”
Section: Hypoxia and Receptor Density Animal Studiesmentioning
confidence: 96%